Contribution of immunophenotype to the investigation and differential diagnosis of Burkitt lymphoma, double‐hit high‐grade B‐cell lymphoma, and single‐hit MYC‐rearranged diffuse large B‐cell lymphoma. Issue 5 (4th June 2020) - Tsagarakis, Nikolaos J.; Papadhimitriou, Stefanos I.; Pavlidis, Dimitris; Liapis, Konstantinos; Gortzolidis, Georgios; Kostopoulos, Ioannis V.; Marinakis, Theodoros; Paterakis, Georgios
Abstract: Background: There are no immunophenotypic guidelines for the investigation of MYC ‐rearranged lymphomas. We aimed to identify simple immunophenotypic features that would help to differentiate between MYC ‐rearranged lymphomas and guide cytogenetic analysis. Methods: We reviewed diagnostic samples from patients diagnosed with Burkitt lymphoma (BL), double‐hit lymphoma (DHL), MYC ‐rearranged diffuse large B‐cell lymphoma (MYC‐DLBCL), and standard (non‐ MYC ‐rearranged) DLBCL over the last decade in our Institution. Using flow cytometry (with antibodies CD20, CD10, CD38, bcl‐2, Ki‐67, FMC‐7, CD43, CD27, CD79b, CD23, and CD22) we determined antigen% expression and median‐fluorescence intensity ratios (MFIR). The forward scatter (FS) and side scatter (SS) characteristics of tumor B‐cells were compared with normal T‐cells (B/T ratios) for patients with MYC ‐rearranged lymphomas. Results: We identified 51 patients of whom 14 had BL, 10 had DHL (6 MYC +/ BCL2 +; 4 MYC +/ BCL 6+), 8 MYC‐DLBCL, and 19 standard DLBCL. The significant differences ( p <.05) were: higher CD38% in BL than standard DLBCL; higher CD10% in BL and DHL versus MYC‐DLBCL and standard DLBCL; higher CD10MFIR in BL than MYC‐DLBCL and standard DLBCL; higher Ki‐67% in BL than DHL and MYC‐DLBCL; higher bcl‐2% in DHL than BL; higher FMC‐7% in BL than MYC‐DLBCL and standard DLBCL; and lower SS (B/T) ratio in DHL than MYC‐DLBCL. Conclusions: The combination of CD38% > 90, CD10% > 80, CD10MFIR > 10, bcl‐2% < 30, and Ki‐67% > 70 was characteristic of BL. "Deviation" from these cut‐offs should raise suspicion for DHL and, therefore, BCL2 and/or BCL6 FISH is required. We also found that a diagnosis of DHL rather than of MYC‐DLBCL was significantly associated with CD10% > 60, Ki‐67% > 50, and SS (B/T) <1.5.